The Implementation of the Structural Analytic Synthetic (SAS) Method to Improve Reading Skills of Grade 2 Students at UPT SD Negeri 006 Langgini - Rahmasari, Venno Rila; Nurhaswinda, Nurhaswinda (TOFEDU: The Future of Education Journal, 2025)
This study was prompted by the inadequate reading abilities of two-grade children at UPT SD Negeri 006 Langgini who failed to meet the Minimum Completeness Criteria (KKM) of 75. Out of 25 pupils, none achieved the KKM. There are 11 students, which represents 50% of the total, and 11 students who have finished their tasks, also accounting for 50%. This research intends to enhance the reading proficiency of two-grade children at UPT SD Negeri 006 Langgini. This study employs the classroom action research (PTK) technique, conducted in two cycles, with each cycle consisting of preparation, action, observation, and reflection stages. The research findings on the utilization of the SAS method with flashcard media were effectively applied and shown an enhancement in students' reading abilities compared to previous levels. The progress can be observed in each cycle's meetings: the first meeting of cycle I showed 63.63% development, the second meeting of cycle I showed 72.72% development, the first meeting of cycle II showed 81.81% development, and the second meeting of cycle II showed 86.36% completion, meeting the expected progress.